Role and Strategy of Hotel Public Relations in Returning Guests After Selat Sunda Tsunami - Widya Nur Bhakti Pertiwi; Diqbal Satyanegara; Asmi Ayuning Hidayah (Jurnal Sosial Humaniora, 2020)
The purpose of this research is to figure out the role of public relations, as wellas the strategy of public relations in the effort to improve the hotel occupancyrate in Anyer, Serang, Banten after the Selat Sunda tsunami. The methodologyused in this study is a qualitative descriptive approach, with in-depthinterviews to collect data. This method of data collection is commenced byinterviews with hotel managers in Anyer. The samples of this research are fivehotels in Anyer Serang, Banten, to represent their respective classes: five-starhotels, four-stars, three-star, and budget hotels. The results of this study showthat the PR of the hotels in Anyer have done their role well, but they have notbeen able to increase the maximum number of room occupancy of the hotelsin Anyer, Serang, Banten.